Street foods in Accra, Ghana: how safe are they? - Patience Mensah; Dorothy Yeboah-Manu; Kwaku Owusu-Darko; Anthony Ablordey (Bulletin of the World Health Organization)
OBJECTIVE: To investigate the microbial quality of foods sold on streets of Accra and factors predisposing to their contamination. METHODS: Structured questionnaires were used to collect data from 117 street vendors on their vital statistics, personal hygiene, food hygiene and knowledge of foodborne illness. Standard methods were used for the enumeration, isolation, and identification of bacteria. FINDINGS: Most vendors were educated and exhibited good hygiene behaviour. Diarrhoea was defined as the passage of > or = 3 stools per day) by 110 vendors (94.0%), but none associated diarrhoea with bloody stools; only 21 (17.9%) associated diarrhoea with germs. The surroundings of the vending sites were clean, but four sites (3.4%) were classified as very dirty. The cooking of food well in advance of consumption, exposure of food to flies, and working with food at ground level and by hand were likely risk factors for contamination. Examinations were made of 511 menu items, classified as breakfast/snack foods, main dishes, soups and sauces, and cold dishes. Mesophilic bacteria were detected in 356 foods (69.7%): 28 contained Bacillus cereus (5.5%), 163 contained Staphylococcus aureus (31.9%) and 172 contained Enterobacteriaceae (33.7%). The microbial quality of most of the foods was within the acceptable limits but samples of salads, macaroni, fufu, omo tuo and red pepper had unacceptable levels of contamination. Shigella sonnei and enteroaggregative Escherichia coli were isolated from macaroni, rice, and tomato stew, and Salmonella arizonae from light soup. CONCLUSION: Street foods can be sources of enteropathogens. Vendors should therefore receive education in food hygiene. Special attention should be given to the causes of diarrhoea, the transmission of diarrhoeal pathogens, the handling of equipment and cooked food, hand-washing practices and environmental hygiene.